2021
DOI: 10.1183/23120541.00170-2020
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory subtype of relapsing polychondritis frequently presents as difficult asthma: a descriptive study of respiratory involvement in relapsing polychondritis with 13 patients from a single UK centre

Abstract: IntroductionRelapsing Polychondritis (RP) is a rare multisystem vasculitis characterised by recurrent cartilage inflammation. Respiratory involvement, of which tracheobronchomalacia (TBM) is the commonest form, is difficult to treat and is linked to increased mortality. We describe 13 patients with respiratory involvement.MethodsThis is a retrospective study of all the patients with RP at University Hospitals Coventry and Warwickshire NHS Trust (UHCW), a secondary care provider for ∼500 000. Only patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Prior reports revealed that additional investigations, such as CT and endoscopy of the neck and chest, can be applied for the early diagnosis and differential diagnosis of relapsing polychondritis. [16][17][18] In our study, the rate of positive chest CT examination findings, namely varying degrees of airway thickening, stenosis and calcification, was 88.9 per cent in airway-affected patients. The predominant symptom was thickening of the main bronchial wall, which is concordant with the findings of Wang et al 13 Bronchoscopy exhibited findings that were positive for airway involvement in 85.7 per cent of patients.…”
Section: Discussionmentioning
confidence: 77%
“…Prior reports revealed that additional investigations, such as CT and endoscopy of the neck and chest, can be applied for the early diagnosis and differential diagnosis of relapsing polychondritis. [16][17][18] In our study, the rate of positive chest CT examination findings, namely varying degrees of airway thickening, stenosis and calcification, was 88.9 per cent in airway-affected patients. The predominant symptom was thickening of the main bronchial wall, which is concordant with the findings of Wang et al 13 Bronchoscopy exhibited findings that were positive for airway involvement in 85.7 per cent of patients.…”
Section: Discussionmentioning
confidence: 77%
“…AZA showed overall response rates ranging from 38 to 100% and CYC from 25 to 100%. In the study by Dubey et al (13), the poor outcome observed with CYC may be explained by its use in refractory disease. Too few patients were exposed to other molecules to draw any conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The average time from onset to diagnosis has been reported to be 2.9 years, and approximately one-third of patients are reported to have visited more than five doctors before diagnosis [7]. Further, RP can be misdiagnosed as bronchial asthma [8]. There are several case reports where the patients had already developed tracheobronchomalacia at the time of the diagnosis of RP [9,10].…”
Section: Discussionmentioning
confidence: 99%